Analysis of patients with septal abscess caused by electrocauterization of the nasal septum - Akyigit, Abdulvahap; Keles, Erol; Karlidag, Turgut; Kaygusuz, Irfan; Yagmahan, Mehmet Salih; Yalcin, Sinasi (Dergipark Akad, 2020)
Objective: Although nasal septal abscesses are mostly caused by trauma, they may occur due to non-traumatic causes. In the present study, we aimed to review patients who underwent electrocauterization of the nasal mucosa for epistaxis and subsequently developed a nasal septal abscess. Methods: The study included 11 patients who underwent nasal electrocauterization for epistaxis and were subsequently admitted to our clinic with a pre-diagnosis of septal abscess for drainage of the abscess. The medical records of the patients, including details such as age, sex, duration of follow-up, symptoms, chronic diseases, microbiological cultures, radiological investigations and complications were retrospectively evaluated. Results: Of the 11 patients included, seven were male and four were female with a mean age of 66.18 +/- 3.7 years. The mean duration of follow-up was 29.09 +/- 17.5 months; five patients had both hypertension and diabetes mellitus, three patients had only diabetes mellitus and three patients had only hypertension. Microbiological culture of the purulent material collected during septal abscess drainage revealed no bacterial growth in six patients, growth of Staphylococcus aureus in two patients and growth of Corynebacterium amycolatum in one patient. Four patients underwent preoperative computed tomography (CT) of the paranasal sinuses and five patients developed a saddle nose deformity in the long-term follow-up. Conclusion: All surgical interventions to the nose or cauterization procedures should be performed under sterile conditions, especially in patients with chronic diseases, and such patients should be followed up after the procedure.
Keywords: Septal abscess; epistaxis; electrocauterization